The Role of Institutional Support in Influencing Environmental Attitudes Through Environmental Awareness in the Palm Oil Processing Industry in West Sumatra - Candrianto Candrianto; Isra Mouludi; Ester Edwar; Mia Ayu Gusti (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
Despite its strategic role in the Indonesian economy, the palm oil processing industry also has the potential to create significant environmental problems and is facing increasing pressure to adopt environmental practices due to sustainability concerns and regulatory demands. In this context, institutional support is considered crucial in shaping pro-environmental behaviour. However, empirical studies explaining how institutional support shapes environmental awareness and attitudes are still limited, particularly in the palm oil industry in developing regions. Furthermore, institutional support in developing countries, including Indonesia, remains diverse and has not yet fully supported sustainable practices at the organizational level. Therefore, this study aims to explore the potential impact of institutional support on shaping environmental attitudes through environmental awareness, thus providing managerial implications for palm oil industry managers in West Sumatra, Indonesia. This study uses organizational level analysis, with data obtained from managers as a representation of the organization collected through a survey of 112 managers working in palm oil processing companies in West Sumatra using purposive sampling and analysed using variance-based structural equation modelling. The results of the study indicate that institutional support has a significant positive effect on environmental awareness (? = 0.666, t = 13.079, p < 0.000) and environmental attitudes (? = 0.573, t = 10.475, p < 0.000). Environmental awareness also has a significant positive effect on environmental attitudes (? = 0.716, t = 8.184, p < 0.000), and environmental awareness partially mediates the relationship between institutional support and environmental attitudes (? = 0.532, t = 9.512, p < 0.00). Based on these findings, it is important to strengthen environmental governance through regulations as a reflection of institutional support. Therefore, policymakers and industry stakeholders are encouraged to strengthen institutional systems to accelerate the process of change towards environmentally friendly practices.